Religious-Ecocentrism Sustainability Accounting: Beyond Utopia towards Universe Sustainability - I Gusti Ayu Agung Omika Dewi (Yayasan Rumah Peneleh, 2021)
This article aims to construct a research methodology in the field of Sustainability Accounting (SA) which refers to the concept of deep ecology based on eco-centrism as well as a religious holistic based on universal values of religious teachings. The construction was carried out to